Develop Interpersonal Intelligence based on Islamic Parenting - Silvia Nurul Afifah; Noor Mua’allimah; Fitri Nihayatun Nadziroh (Early Childhood Education Development and Studies (ECEDS), 2022)
We write this journal on developing interpersonal intelligence based on Islamic parenting to find out and explain in more detail and develop the understanding of interpersonal intelligence and how it is applied in Islamic parenting. the purpose of this study is to apply Islamic parenting by developing children's interpersonal intelligence. This research uses a literature review method. which materials we take can be obtained from various reading books and various educational journal publications. Character will be formed as a result of understanding three relationships that must be experienced by every human being, namely the relationship with oneself, the environment, and the relationship with God. Each result of the relationship will provide a meaning or understanding which ultimately becomes the child's values ​​and beliefs. How children understand the form of these relationships will determine how children treat the world. Negative understanding will have an impact on negative treatment and positive understanding will treat the world positively. Positive understanding in children from an early age is one of them by giving children confidence in themselves, helping children direct their potential, so they are better able to explore on their own, not pressing it either directly or subtly, and so on. Get used to children socializing and interacting with the surrounding environment so that the formation of children's character to improve interpersonal intelligence can grow well.